Legal Protection of Child Victims of Pedophilia (Case Study: 375/Pid.Sus/2021/PN Skt) - Muhammad Dafa Pristian Naufal; Bambang Sukoco (Universitas Muhammadiyah Surakarta, 2023)
The crime of pedophilia is a form of sexual deviation that uses minors as sexual objects. The formulation of the problem in this study, How is the Legal Protection of Child Victims of Pedophilia Criminal Acts according to Legislation?, How does Islamic Law view the crime of Pedophilia?, What are the judges' legal considerations as a form of Protection of Pedophilia? Child Victims of Pedophilia in case Number 375/Pid.Sus/2021/PN Skt. The research methods used in this research include juridical normative legal research methods. Data collection for this research includes library research and interviews. The results of data analysis are carried out in a qualitative descriptive manner and draw conclusions in an inductive manner. The results of this study will be decided in case verdict Number: 375/Pid.Sus/2021/PN Skt. The defendant in this case has violated Article 81 paragraph (2) in conjunction with Article 76 D of Law Number 17 of 2016 concerning Amendments to Law Number 23 of 2002 concerning Child Protection. The role of the family, school, or community is needed by providing religious values for children and socialization about the impact of pedophilia. For law enforcement officials, in handling pedophilia cases, it must be resolved thoroughly and fairly, both fair to the perpetrators, and fair to the victims of pedophilia.